Inverted electro-mechanical behaviour induced by the irreversible domain configuration transformation in (K,Na)NbO3-based ceramics - Huan, Yu; Wang, Xiaohui; Koruza, Jurij; Wang, Ke; Webber, Kyle Grant; Hao, Yanan; Li, Longtu (Scientific Reports, 2016)
Miniaturization of domains to the nanometer scale has been previously reported in many piezoelectrics with two-phase coexistence. Despite the observation of nanoscale domain configuration near the polymorphic phase transition (PPT) regionin virgin (K-0.5,Na-0.5)NbO3 (KNN) based ceramics, it remains unclear how this domain state responds to external loads and influences the macroscopic electromechanical properties. To this end, the electric -field -induced and stress -induced strain curves of KNNbased ceramics over a wide compositional range across PPT were characterized. It was found that the coercive field of the virgin samples was highest in PPT region, which was related to the inhibited domain wall motion due to the presence of nanodomains. However, the coercive field was found to be the lowest in the PPT region after electrical poling. This was related to the irreversible transformation of the nanodomains into micron -sized domains during the poling process. With the similar micron -sized domain configuration for all poled ceramics, the domains in the PPT region move more easily due to the additional polarization vectors. The results demonstrate that the poling process can give rise to the irreversible domain configuration transformation and then account for the inverted macroscopic piezoelectricity in the PPT region of KNN-based ceramics.